6q25.1 (TAB2) microdeletion syndrome: Congenital heart defects and cardiomyopathy. Issue 7 (2nd May 2017) - Cheng, Andrew; Dinulos, Mary Beth P.; Neufeld‐Kaiser, Whitney; Rosenfeld, Jill; Kyriss, McKenna; Madan‐Khetarpal, Suneeta; Risheg, Hiba; Byers, Peter H.; Liu, Yajuan J.
Abstract : Congenital heart defects (CHD) are the most frequent type of congenital anomaly and are often associated with genetic and chromosomal syndromes. Haploinsufficiency of TAB2 ( TGF‐beta activated kinase 1/MAP3K7 binding protein 2 ) has been proposed to cause valvular and cardiac outflow tract structural abnormalities. In this study, we describe 13 newly identified individuals with microdeletions of chromosome 6q25.1 that involve TAB2 . One of the patients in our study cohort has the smallest deletion yet reported, affecting only TAB2 . These were compared to 27 other patients reported in the published literature or DECIPHER to have similar microdeletions, for a total study group of 40 patients. Our study shows that individuals with TAB2 deletions are predisposed to developing a primary cardiomyopathy with reduced systolic function, even in the absence of CHD. Our study cohort also shares a number of non‐cardiac phenotypic findings: characteristic dysmorphic facial features, intrauterine growth restriction and/or postnatal proportionate short stature, hypotonia, developmental delay and/or intellectual disability, and connective tissue abnormalities. We conclude that a microdeletion of 6q25.1 that includes TAB2 causes a distinctive, multi‐systemic syndrome. The 6q25.1 microdeletion syndrome should be considered in a patient with cardiomyopathy or a CHD, especially valve and/or atrial or ventricular septal abnormalities, and with phenotypic features described in this study. We recommend that patients with a TAB2 deletion be screened longitudinally for systolic heart failure, even if an initial echocardiogram is normal.